1977
DOI: 10.1037/0278-7393.3.6.712
|View full text |Cite
|
Sign up to set email alerts
|

Serial recall and the modality effect: Effects of word frequency.

Abstract: Serial position curves for the immediate serial recall of supraspan word lists were investigated as a joint function of input modality and the frequency with which the list words occur in everyday usage. There was a strong effect of frequency at primacy positions but no effect at recency positions. It is concluded from this interaction that, contrary to some views, serial recall is not the product of a simple, unitary process. The modality effect, which is confined to recency positions, was independent of word… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
88
3
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 21 publications
10
88
3
2
Order By: Relevance
“…The complexity of the relationship between list composition, item arrangement, and the frequency effect is heightened by the possibility that directional associativity exists throughout recall but is masked for late serial positions by the relative efficiencies or costs that arise from previous output. The findings reinforce the claim that the serial recall task is not as simple as it may seem on the surface (Watkins & Watkins, 1977), and teasing apart the processes that contribute to serial recall at different points in the list poses a considerable challenge.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…The complexity of the relationship between list composition, item arrangement, and the frequency effect is heightened by the possibility that directional associativity exists throughout recall but is masked for late serial positions by the relative efficiencies or costs that arise from previous output. The findings reinforce the claim that the serial recall task is not as simple as it may seem on the surface (Watkins & Watkins, 1977), and teasing apart the processes that contribute to serial recall at different points in the list poses a considerable challenge.…”
supporting
confidence: 78%
“…While tasks involving pure lists of either only high-frequency (HF) or only low-frequency (LF) words have shown a clear advantage for HF words across many replications (Allen & Hulme, 2006;Hulme et al, 1997;Hulme et al, 2003;Morin et al, 2006;Poirier & Saint-Aubin, 1996;Stuart & Hulme, 2000;Roodenrys, Hulme, Lethbridge, Hinton, & Nimmo, 2002;Roodenrys & Quinlan, 2000;SaintAubin & LeBlanc, 2005;Saint-Aubin & Poirier, 2005;Watkins & Watkins, 1977), the results of experiments using mixed lists, where HF and LF words appear together on the same trial, indicate that under some conditions, LF items can be recalled as well as HF words (Hulme et al, 2003;Morin et al, 2006;Saint-Aubin & LeBlanc, 2005).…”
mentioning
confidence: 99%
“…In line with this idea, Wagner (1974) observed that unschooled people from rural Yucatan, Mexico, did not show the primacy effect in ordered memory of pictures (i.e., better recall of initial list compared to middle list items, usually observed in literate adults; Atkinson & Shiffrin, 1968). Although its interpretation has been highly debated (e.g., Brown et al, 2000;Nairne, Neath, Serra, & Byun, 1997;Oberauer, 2003), the primacy effect in serial position curves is sometimes assumed to reflect greater or more elaborative rehearsal of earlier list items, facilitating transfer of items to LTM and subsequent retrieval (e.g., Flavell, 1970;Hagen, 1971;Tulving & Craik, 2000;Watkins & Watkins, 1977). Hence, Wagner concluded that rural, unschooled people are not using verbal rehearsal strategies, which may explain the lack of increase in developmental performance (with participants aged from 7 to 35 years) he also observed in that population.…”
Section: Verbal Recoding and Rehearsal Strategiesmentioning
confidence: 99%
“…This lexical/semantic contribution explains why normal immediate serial recall (ISR) is better for (1) words vs. nonwords (e.g., Brener, 1940;Hulme, Maughan, & Brown, 1991; referred to as the effect of "lexicality" below); (2) high compared with low frequency words (Gregg, Freedman, & Smith, 1989;Hulme et al, 1997;Roodenrys & Quinlan, 2000;Watkins & Watkins, 1977); (3) imageable/concrete words vs. abstract words (Bourassa & Besner, 1994;Walker & Hulme, 1999); and (4) semantically grouped vs. ungrouped words (Poirier & Saint-Aubin, 1995;Saint-Aubin & Poirier, 1999).…”
Section: Introductionmentioning
confidence: 99%